Genetic improvement of clubroot resistance in the recessive genic male sterile line YA001 in Brassica napus - Jiang, Yingfen; Fei, Weixin; Wu, Xingjie; Chen, Fengxiang; Li, Wenjing; Wang, Ying; Zhan, Lanlan; Li, Cheng (Frontiers in Plant Science, 2025)
Clubroot disease poses a serious challenge to global rapeseed production, including major growing regions in China. Introgressing clubroot-resistant (CR) genes into rapeseed is an efficient way to prevent the spread of this disease. YA001 is a stable recessive genic male-sterile (RGMS) three-line system in Brassica napus with good combining ability but high susceptibility to clubroot. To improve the clubroot-resistant of YA001, ‘Bing409R’, which exhibits excellent disease resistance and contains the CR gene CRb, was used as the donor parent, and the male-sterile line YA001 was used as the female parent for hybridization in Anhui Province. The temporary maintainer line of YA001 was then used as the recurrent parent for backcrossing. Marker assistant selection was conducted for the CR gene and fertility-related genes. In each backcrossing generation, individuals with the genotype RrMs3ms3RfbRfc were selected. After 4 generations of backcrossing, self-pollination was performed, and homozygous CR RGMS three-lines were developed from the self-pollinated progeny. Inoculation tests under controlled conditions showed that the disease index of improved YA001 was 8.7, exhibited high clubroot resistance. Hybrid combinations developed by CR YA001 demonstrated superior yield performance and effective disease resistance when cultivated in infested region. And the highest-yielding of CR combinations achieved 3273.15 kg/ha while susceptible control was only 1279.8 kg/ha. This study provides a rapidand efficient method for breeding homogeneous CR RGMS three-lines. Furthermore, these developed lines serve as an important genetic resource for the high-throughput selection of strong heterosis and CR combinations, thereby contributing to the control of clubroot spread.